2017
DOI: 10.1002/jmv.24901
|View full text |Cite
|
Sign up to set email alerts
|

Identification of group B rotavirus as an etiological agent in the gastroenteritis outbreak in Maharashtra, India

Abstract: Acute gastroenteritis outbreak occurred at Pargaon, Maharashtra, India in 1789 cases with an attack rate of 32.5% between November to December 2015. The stool specimens (n = 32) were investigated for different enteric viral agents using conventional methods. Transmission electron microscopy and RNA polyacrylamide gel electrophoresis respectively identified morphologically distinct rotavirus particles in 28% and RNA migration pattern of Group B Rotavirus (GBR) in 72% of the specimens. Reverse transcription poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…A unique amino acid substitution at the VP7‐76 position (Lysine→Arginine) was noted similar to Chinese lineage strains (ADRV/1982, WH‐1/2002). This observation is in concordance with earlier outbreak reported from Pargaon, Western India in 2015 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A unique amino acid substitution at the VP7‐76 position (Lysine→Arginine) was noted similar to Chinese lineage strains (ADRV/1982, WH‐1/2002). This observation is in concordance with earlier outbreak reported from Pargaon, Western India in 2015 …”
Section: Discussionsupporting
confidence: 93%
“…The restriction of RVB outbreaks mainly to adolescent and adult age group individuals was observed in the present study similar to earlier reports from India and China . Lahon et al suggested that the low infection rates observed in children may be due to either low exposure of children or fecal shedding of the virus below the detection limit of the assay employed in the study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations